Spor Alemi (1919-1929): A Turkish sports magazine in the transition period from The Ottoman Empire to The Turkish Republic - Eroğul, Ali. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
In this thesis, stages of development of sports, especially football in the last years of the Ottoman Empire and the early years of the Turkish Republic in the framework of the Spor Alemi magazine (1919-1929). For this purpose, all available issues of the magazine have been scanned, examnined and indexed. The stance of the magazine concerning current sports discussions has been looked into; its approach to various sports such as boxing, rowing and billiards has been examined. Football has been the focus of the thesis while also looking at how the official football policies were applied. In that context, news items and articles published in the magazine have been studied; examples of football news from Istanbul, the West and Anatolia have been cited. Therefore, this study aims not only to shed a light on Spor Alemi (1919-1929), but also on the history of Turkish football itself.|Keywords: Sport Periodicals in Ottoman, Football, the Ottoman Empire, Sports, Spor Alemi.
Keywords: Sports -- Turkey -- History.; Football -- Turkey -- History.